Growth, biomass, and chlorophyll-a and carotenoid content of Nannochloropsis sp. strain BJ17 under different light intensities - Fakhri, Muhammad; Arifin, Nasrullah Bai; Hariati, Anik Martina; Yuniarti, Ating (Indonesian Society of Scientific Aquaculture (ISSA), 2017)
ABSTRACT Nannochloropsis sp. has been identified as sources of live feed and pigment in aquaculture. To increase the production, the optimal environmental conditions for microalgae are required. Light intensity is one of the important factors that significantly affects the biomass and pigment of microalgae. The study aimed to determine the effect of light intensity (1,500; 3,000; and 4,500 lux) on growth, biomass production, chlorophyll-a, and carotenoid content of Nannochloropsis sp. strain BJ17. The results showed that different light intensities significantly affected the growth, biomass, chlorophyll-a and carotenoid contents of Nannochloropsis sp. strain BJ17. Increasing light intensity resulted in the increase of the growth rate, biomass, chlorophyll-a, and carotenoid contents of Nannochloropsis sp. strain BJ17. The cell achieved the highest specific growth rate of 1.729 %/day and the cell concentration of 43.333×106 cell/mL at a light intensity of 4,500 lux. The highest chlorophyll-a and carotenoid concentrations of algae were obtained at 4,500 lux (8.304 μg/mL and 3.892 μg/mL, respectively). This study suggested that increasing light intensity led to the increase in the growth, biomass, chlorophyll-a, and carotenoid content of Nannochloropsis sp. strain BJ17. Keywords: carotenoid, chlorophyll, biomass, growth rate, light intensity ABSTRAK Nannochloropsis sp. diketahui sebagai sumber pakan alami dan pigmen pada budidaya perikanan. Budidaya pada kondisi lingkungan yang optimal diperlukan untuk meningkatkan produksi mikroalga. Intensitas cahaya merupakan salah satu faktor esensial yang secara signifikan mempengaruhi biomassa dan pigmen mikroalga. Tujuan penelitian ini adalah untuk menentukan pengaruh intensitas cahaya yang berbeda (1.500, 3.000, and 4.500 lux) terhadap pertumbuhan, produksi biomassa, klorofil-a, dan karotenoid Nannochloropsis sp. strain BJ17. Hasil menunjukkan bahwa intensitas cahaya yang berbeda berpengaruh secara signifikan terhadap pertumbuhan, biomassa dan klorofil-a dan karotenoid Nannochloropsis sp. strain BJ17. Semakin tinggi intensitas cahaya maka laju pertumbuhan, biomassa, kandungan klorofil-a dan total karotenoid Nannochloropsis sp. strain BJ17 semakin tinggi. Laju pertumbuhan spesifik tertinggi 1,729%/hari dan konsentrasi sel maksimum tertinggi 43,333×106 sel/mL dihasilkan pada intensitas cahaya 4.500 lux. Konsentrasi klorofil-a (8,304 μg/mL) dan karotenoid (3,892 μg/mL) tertinggi juga diperoleh pada intensitas cahaya 4.500 lux. Studi ini menunjukkan bahwa peningkatan intensitas cahaya berperan dalam meningkatkan pertumbuhan, produksi biomassa, klorofil-a, dan karotenoid Nannochloropsis sp. strain BJ17. Kata kunci: karotenoid, klorofil, biomassa, pertumbuhan, intensitas cahaya